Perkembangan Sel Endometrium Domba setelah Inkubasi dalam Kolagenase dan Dikultur In Vitro dengan Estradiol dan Progesteron - Ananda, Ananda; Kaiin, Ekayanti Mulyawati; Karja, Ni Wayan Kurniani; Setiadi, Mohamad Agus (Jurnal Veteriner; Vol 20 No 3 (2019)DO - 10.19087/jveteriner.2019.20.3.298, 2019)
The aim of the present study was to determine the optimal incubation time of collagenase on concentration, viability, quality of endometrial cell culture, and the role of estradiol and progesterone on ovine endometrial cells proliferation. Endometrium minced was incubated into collagenase with different duration of time: 1 hour, 3 hours, and 6 hours repectively. Cell concentration and viability were calculated after incubation. The quality of cell culture was observed on 1st, 3rd, and 5th day after seeding. The best incubation result was then continued with the addition of the E2 (100 pg/ mL), P4 (100 ng/mL), E2:P4 (100 pg/mL : 10 ng/mL), and E2:P4 (10 pg/mL : 100 ng/mL) into the culture medium. After nine days, cell culture was harvested by trypsinization. Concentration and cell viability were analyzed using analysis of variance, followed by Duncan test. Quality of endometrial cell culture was analyzed descriptively. Results showed that there was a significant decreased in the concentration and cell viability obtained in each treatment of collagenase incubation time and optimum treatment of endometrial cell culture was found at 3 hours. Experiment on culture of endometrial cell revealed that proliferation rate treated by E2 and P4 was better then control (P<0.05). Futhermore, additional of E2 into the culture medium even E2 alone (100 pg/mL or higher E2 combination with P4 (100 pg/mL : 10 ng/mL) showed better proliferation rate than P4 alone (100 ng/mL) or higher P4 combination (10 pg/mL : 100 ng/mL). In conclusion, suplementation of 100 pg/mL of estradiol (E2) could support better proliferation of ovine endometrial cells in vitro.